Penerapan Prinsip Good Government Governance Dalam Pengelolaan Alokasi Dana Desa - Ana Bidayatul Maulida; Arik Susbiyani; Astrid Maharani (Politeknik Negeri Jember, 2021)
Good government governance is good governance. This concept has been applied in the government sector to strengthen village autonomy. This study aims to analyze and describe the application of good government governance principles in managing village fund allocations in Ambulu village and to find out whether the management of village fund allocations in Ambulu village has met the principles of good government governance. This type of research was conducted with a qualitative method using a descriptive approach. The object of this research is the Ambulu Village Government located in Ambulu District, Jember Regency. The results of this study indicate that the Ambulu Village Government system has been running well and has met all indicators of good government governance (democracy, transparency, accountability, legal culture, as well as fairness and equality). The Ambulu Village Government has implemented the five principles of good government governance in real terms so that it can realize a government system with good governance. Good government governance that runs well can prosper the entire community equally. Keywords: Good Government Governance, Village Fund Allocation, Democracy, Accountability, Transparency